Cyclic piezoresistive effect in poly(dimethylsiloxane)/carbon nanofiber composites for large strain Sensing applications. (April 2019) - Lu, M; Chen, MH; Bu, ZX; Wang, LS; Sun, L
Adding conductive one-dimensional carbon nanomaterials to poly(dimethysiloxane) can form bio-compatible composites with significant electromechanical (piezoresistive) response. This effect can be effectively tuned by controlling the carbon nanofiller size, concentration, and distribution. However, to be applied as strain sensors, the composite material has to meet mechanical, sensitivity, temperature stability, and reliability requirements. Here we report on the study of cyclic electromechanical behaviors of poly(dimethysiloxane)/carbon nanofiber composites under different temperatures. Through mechanical training, reproducible and sensitive piezoresistive response suitable for large strain sensing can be obtained.